Influence of Visual Complexity on Chinese Cultural Elements and Processing Fluency on Purchase Intention in Chinese Luxury Fashion Brands - Wang, Zheng; Ringah, Kanyan; Musdi, Shanat (UNIMAS, 2024)
The research examines the relationship between the degree of visual complexity and the purchase intention of Chinese consumer towards Chinese domestic luxury fashion brands. The study explores the shifting consumer preferences towards local luxury brands. The research aims to addresses a significant gap in the existing literature, specifically the limited study and understanding of how visual complexity impacts the purchase intentions of Chinese luxury fashion brands. It centres on a key element of brand identity, particularly the logomark—to investigate how the visual complexity of Chinese cultural elements affects processing fluency and, in turn, influences consumer purchase intention. The study is grounded in processing fluency theory and examines how the visual complexity of Chinese cultural elements impacts processing fluency (both perceptual and conceptual), the moderating role of prior exposure on this relationship, and the mediating effect of processing fluency on the purchase intention of Chinese luxury fashion items. Utilizing three quantitative surveys and overall, 545 participants for empirical investigation, as well as focus on the Chinese knot. The findings from the three studies indicate that visual complex elements have negative effect on processing fluency, and prior exposure has partial effect on visual complexity and processing fluency; the visual complexity both directly and indirectly impact on purchase intentions. These findings contribute theoretically to the processing fluency theory and the understanding of purchase intentions. The research significance offers practical guidance for practitioners such as brand managers and designers in handling the visual identity of Chinese luxury fashion brands.